Defaulting from Care and Quality of Life of Adults on Anti-Retroviral Treatment Program in Owo, Ondo State, Nigeria: A Case-Control Study - Olayinka Stephen Ilesanmi; Ikeola A. Adeoye; Olufunmilayo I. Fawole (Shiraz University of Medical Sciences, 2021)
Background: In Nigeria, over 600,000 people living with HIV/AIDS (PLWHA) are on antiretroviral therapy (ART) as of 2020. Defaulters after commencing ART range between 10-36%. This study identified the factors associated with default from ART and quality of life among PLWHA. Methods: An unmatched case-control study was conducted among 102 cases and 204 controls at the Federal Medical Centre, Owo, Ondo State, Nigeria. Cases were adults on ART who had defaulted from care and missed at least two consecutive appointments in the last year, while controls were adults on ART who had been consistent with clinic attendance for at least one year. Chi-square test, t-test, and binary logistic regressions were used to identify the predictors of default at a 95% confidence interval.  Results:Respondent's mean age was 41.4±10.3 years while 61.4% of the respondents were females. ART role in reducing viral load was described correctly by 66 (64.7%) cases and 155 (76.0%) controls (p=0.04). The quality of life in the physical domain was 15.3± 3.4 among cases and 16.6±3.0 among controls (p=0.001). Defaulting from treatment was associated with non-disclosure of status to a partner (AOR: 2.8; CI 95%: 1.6-4.9), receiving fewer counseling sessions (AOR: 2.3; CI 95%: 1.3-4.2), poor perception of the quality of health care services (AOR: 2.6; CI 95%: 1.4-4.7), suboptimal quality of life (AOR: 2.7; CI 95%: 1.5- 4.8) and the richer wealth index (AOR: 1.8; CI 95%: 1.01-3.18). Conclusion: Inclusion of discussions on disclosure during counseling sessions was recommended to reduce default.